The moral intelligence of the Arab university professor in the light of gender, nationality, and teaching experience: a cross-cultural factor study between Egypt and Algeria to test the validity of the Borba theory - Kheddouci, Karima; Abd El Wahed Yousef, Soliman; Fadhli, Ahmed (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
The study aimed to uncover the nature of the factor structure of moral intelligence for the Arab university professor in the light of gender, nationality, and teaching experience, as a step to test the validity of the Borba theory of moral intelligence. By applying a measure of moral intelligence to the Arab university professor in the light of the Borba theory, the researchers prepared a basic sample of (500) professors, assistant professors, higher education professors, and lecturers professors A, by some Egyptian and Algerian public and private universities, and by using confirmatory and exploratory factor analysis The study found that the moral intelligence of the Arab university professor includes one general underlying factor around which the seven observing factors are organized, in addition to the absence of statistically significant differences in moral intelligence due to gender, nationality, and teaching experience.